2017
DOI: 10.1002/2016wr020203
|View full text |Cite
|
Sign up to set email alerts
|

High‐resolution flow characterization close to the sediment‐water interface in a run of the river reservoir

Abstract: A bistatic high‐resolution acoustic profiler was used in order to characterize the lowermost boundary layer of a run of the river reservoir. The profiler allows determining the statistics of the three‐dimensional flow field at a single point (sweet spot) as well as the measurement of the time averaged flow velocity profiles at 1 mm resolution around the sweet spot. Therefore, in addition to the flow statistics provided by single point acoustic Doppler profilers, mixing coefficients as well as production of tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Such rotations were small, typically <4° from horizontal. Brand and Noss () suggested that rotating the horizontal velocities to the mean current direction reduces bias induced by small but unavoidable misalignments in instrument orientation during deployment.…”
Section: Field Experiments and Methodsmentioning
confidence: 99%
“…Such rotations were small, typically <4° from horizontal. Brand and Noss () suggested that rotating the horizontal velocities to the mean current direction reduces bias induced by small but unavoidable misalignments in instrument orientation during deployment.…”
Section: Field Experiments and Methodsmentioning
confidence: 99%